Unveiling the giant polarisation ratio of chiral photoluminescence in MoS2 nanorolligami fabricated using a centre-to-edge rolling mechanism - Kesarwani, Rahul; Veverka, Miroslav; Žáček, Martin; Varade, Vaibhav; Fekete, Ladislav; Kalbac, Martin; Vejpravova, Jana (Nanoscale horizons, 2025)
We introduced mechanical strain to systematically roll monolayer (1-L) MoS2 into nanostructures with diameters ranging from 100 to 200 nm. The rolled MoS2 regions exhibit unique anisotropic optical behaviour compared to the flat regions (thickness ≤1 nm), as analysed through polarisation-resolved photoluminescence (PL) and Raman spectroscopy. Raman spectroscopy revealed that the E2g/A1g intensity ratio under circular polarisation was approximately 0.25 in the rolled regions, whereas it approached zero in the flat region. These findings highlight pronounced optical anisotropy and symmetry breaking in rolled MoS2, distinguishing it from the isotropic flat regions. Additionally, angular-dependent PL measurements demonstrated a strongly enhanced linear polarisation ratio (LPR) of 28% and a circular polarisation ratio (CPR) of 37% in the rolled regions, indicating strong optical anisotropy. In contrast, the flat MoS2 regions exhibited isotropic behaviour, with LPR and CPR values typically around 8%. Our results demonstrate that rolling-induced localised deformation profoundly modifies exciton polarisation behaviour in MoS2. Enabling precise light filtering and nanoscale manipulation via nanoscrolling of the two-dimensional materials, our work lays the foundation for next-generation optoelectronic devices with tailored optical responses and enhanced functionality.